A comprehensive framework for evaluating key project requirements - Yang, Li-Ren; Chen, Jieh-Haur; Huang, Chung-Fah (Journal of Civil Engineering and Management, 2014)
Requirements definition affects work performed in subsequent phases of a project. Thus, the compliance with requirements is crucial to the success of a project. The primary objective of this research was to develop a comprehensive framework for evaluating key building project requirements. The second objective was to identify and prioritize important project requirement using the analytical network process (ANP). The third objective was to examine the impact of requirement completeness on project success using structural equation model (SEM) analysis. A four-phase approach was employed to achieve the goals. The results suggest that building programming and site information have a higher priority in requirement definition than project control, project strategy, and project design parameter. The findings also indicate that requirement completeness may contribute significantly to building project success in terms of schedule success, cost success, quality performance, and overall benefit.